Management of whitefly transmitted viruses in openfield production systems - Lapidot, M.; Legg, James P.; Wintermantel, William M.; Polston, J.E. (Elsevier, 2014)
Whiteflies are a key pest of crops in open-field production throughout the tropics andsubtropics. This is due in large part to the long and diverse list of devastating plantviruses transmitted by these vectors. Open-field production provides many challengesto manage these viruses and in many cases adequate management has not been possible.Diseases caused by whitefly-transmitted viruses have become limiting factors inopen-field production of a wide range of crops, i.e., bean golden mosaic disease inbeans, tomato yellow leaf curl disease in tomato, cassava mosaic disease and cassavabrown streak disease in cassava, and cotton leaf crumple disease in cotton. While hostresistance has proven to be the most cost-effective management solution, few examplesof host resistance have been developed to date. The main strategy to limit the incidenceof virus-infected plants has been the application of insecticides to reduce vectorpopulations aided to some extent by the use of selected cultural practices. However,due to concerns about the effect of insecticides on pollinators, consumer demandfor reduced pesticide use, and the ability of the whitefly vectors to developinsecticide-resistance, there is a growing need to develop and deploy strategies thatdo not rely on insecticides. The reduction in pesticide use will greatly increase the needfor genetic resistance to more viruses in more crop plants. Resistance combined withselected IPM strategies could become a viable means to increase yields in crops producedin open fields despite the presence of whitefly-transmitted viruses. Whiteflies are a key pest of crops in open-field production throughout the tropics andsubtropics. This is due in large part to the long and diverse list of devastating plantviruses transmitted by these vectors. Open-field production provides many challengesto manage these viruses and in many cases adequate management has not been possible.Diseases caused by whitefly-transmitted viruses have become limiting factors inopen-field production of a wide range of crops, i.e., bean golden mosaic disease inbeans, tomato yellow leaf curl disease in tomato, cassava mosaic disease and cassavabrown streak disease in cassava, and cotton leaf crumple disease in cotton. While hostresistance has proven to be the most cost-effective management solution, few examplesof host resistance have been developed to date. The main strategy to limit the incidenceof virus-infected plants has been the application of insecticides to reduce vectorpopulations aided to some extent by the use of selected cultural practices. However,due to concerns about the effect of insecticides on pollinators, consumer demandfor reduced pesticide use, and the ability of the whitefly vectors to developinsecticide-resistance, there is a growing need to develop and deploy strategies thatdo not rely on insecticides. The reduction in pesticide use will greatly increase the needfor genetic resistance to more viruses in more crop plants. Resistance combined withselected IPM strategies could become a viable means to increase yields in crops producedin open fields despite the presence of whitefly-transmitted viruses. Whiteflies are a key pest of crops in open-field production throughout the tropics andsubtropics. This is due in large part to the long and diverse list of devastating plantviruses transmitted by these vectors. Open-field production provides many challengesto manage these viruses and in many cases adequate management has not been possible.Diseases caused by whitefly-transmitted viruses have become limiting factors inopen-field production of a wide range of crops, i.e., bean golden mosaic disease inbeans, tomato yellow leaf curl disease in tomato, cassava mosaic disease and cassavabrown streak disease in cassava, and cotton leaf crumple disease in cotton. While hostresistance has proven to be the most cost-effective management solution, few examplesof host resistance have been developed to date. The main strategy to limit the incidenceof virus-infected plants has been the application of insecticides to reduce vectorpopulations aided to some extent by the use of selected cultural practices. However,due to concerns about the effect of insecticides on pollinators, consumer demandfor reduced pesticide use, and the ability of the whitefly vectors to developinsecticide-resistance, there is a growing need to develop and deploy strategies thatdo not rely on insecticides. The reduction in pesticide use will greatly increase the needfor genetic resistance to more viruses in more crop plants. Resistance combined withselected IPM strategies could become a viable means to increase yields in crops producedin open fields despite the presence of whitefly-transmitted viruses. Whiteflies are a key pest of crops in open-field production throughout the tropics andsubtropics. This is due in large part to the long and diverse list of devastating plantviruses transmitted by these vectors. Open-field production provides many challengesto manage these viruses and in many cases adequate management has not been possible.Diseases caused by whitefly-transmitted viruses have become limiting factors inopen-field production of a wide range of crops, i.e., bean golden mosaic disease inbeans, tomato yellow leaf curl disease in tomato, cassava mosaic disease and cassavabrown streak disease in cassava, and cotton leaf crumple disease in cotton. While hostresistance has proven to be the most cost-effective management solution, few examplesof host resistance have been developed to date. The main strategy to limit the incidenceof virus-infected plants has been the application of insecticides to reduce vectorpopulations aided to some extent by the use of selected cultural practices. However,due to concerns about the effect of insecticides on pollinators, consumer demandfor reduced pesticide use, and the ability of the whitefly vectors to developinsecticide-resistance, there is a growing need to develop and deploy strategies thatdo not rely on insecticides. The reduction in pesticide use will greatly increase the needfor genetic resistance to more viruses in more crop plants. Resistance combined withselected IPM strategies could become a viable means to increase yields in crops producedin open fields despite the presence of whitefly-transmitted viruses. Whiteflies are a key pest of crops in open-field production throughout the tropics andsubtropics. This is due in large part to the long and diverse list of devastating plantviruses transmitted by these vectors. Open-field production provides many challengesto manage these viruses and in many cases adequate management has not been possible.Diseases caused by whitefly-transmitted viruses have become limiting factors inopen-field production of a wide range of crops, i.e., bean golden mosaic disease inbeans, tomato yellow leaf curl disease in tomato, cassava mosaic disease and cassavabrown streak disease in cassava, and cotton leaf crumple disease in cotton. While hostresistance has proven to be the most cost-effective management solution, few examplesof host resistance have been developed to date. The main strategy to limit the incidenceof virus-infected plants has been the application of insecticides to reduce vectorpopulations aided to some extent by the use of selected cultural practices. However,due to concerns about the effect of insecticides on pollinators, consumer demandfor reduced pesticide use, and the ability of the whitefly vectors to developinsecticide-resistance, there is a growing need to develop and deploy strategies thatdo not rely on insecticides. The reduction in pesticide use will greatly increase the needfor genetic resistance to more viruses in more crop plants. Resistance combined withselected IPM strategies could become a viable means to increase yields in crops producedin open fields despite the presence of whitefly-transmitted viruses. Whiteflies are a key pest of crops in open-field production throughout the tropics andsubtropics. This is due in large part to the long and diverse list of devastating plantviruses transmitted by these vectors. Open-field production provides many challengesto manage these viruses and in many cases adequate management has not been possible.Diseases caused by whitefly-transmitted viruses have become limiting factors inopen-field production of a wide range of crops, i.e., bean golden mosaic disease inbeans, tomato yellow leaf curl disease in tomato, cassava mosaic disease and cassavabrown streak disease in cassava, and cotton leaf crumple disease in cotton. While hostresistance has proven to be the most cost-effective management solution, few examplesof host resistance have been developed to date. The main strategy to limit the incidenceof virus-infected plants has been the application of insecticides to reduce vectorpopulations aided to some extent by the use of selected cultural practices. However,due to concerns about the effect of insecticides on pollinators, consumer demandfor reduced pesticide use, and the ability of the whitefly vectors to developinsecticide-resistance, there is a growing need to develop and deploy strategies thatdo not rely on insecticides. The reduction in pesticide use will greatly increase the needfor genetic resistance to more viruses in more crop plants. Resistance combined withselected IPM strategies could become a viable means to increase yields in crops producedin open fields despite the presence of whitefly-transmitted viruses.